Alternative Oxidase Is Positive for Plant Performance. (July 2018) - Selinski, Jennifer; Scheibe, Renate; Day, David A.; Whelan, James
Abstract : The alternative pathway of mitochondrial electron transport, which terminates in the alternative oxidase (AOX), uncouples oxidation of substrate from mitochondrial ATP production, yet plant performance is improved under adverse growth conditions. AOX is regulated at different levels. Identification of regulatory transcription factors shows that Arabidopsis thaliana AOX1a is under strong transcriptional suppression. At the protein level, the primary structure is not optimised for activity. Maximal activity requires the presence of various metabolites, such as tricarboxylic acid-cycle intermediates that act in an isoform-specific manner. In this opinion article we propose that the regulatory mechanisms that keep AOX activity suppressed, at both the gene and protein level, are positive for plant performance due to the flexible short- and long-term fine-tuning. Highlights: In plant mitochondria, the AOX is a potentially 'energy wasteful' protein that dramatically reduces ATP generation, with most of the energy dissipated as heat, and avoids formation of reactive oxygen species by preventing over-reduction of the electron transport chain. Based on the 'energy wasteful' nature of AOX, this enzyme needs to be regulated on various levels to guarantee a sufficient supply of ATP to cells, but also needs to be activated to counteract oxidative stress. Recent studies have shown that AOX is negatively regulated at a transcriptional level, but activated by latent transcriptional factors that must be activated themselves, and activated at a post-translational level in an isoform-specific manner, to the advantage of the plant. That is, AOX is a potentially 'energetically wasteful' enzyme that is controlled by strong regulatory mechanisms so that it can be harnessed to improve plant performance, in the short and long term.